(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to explain the theoretical framework for the research variables represented by green target cost technology, the product life cycle, and cost reduction, and to study the relationship between these variables and how to apply them in the research sample. This is done by relying on the deductive approach in presenting the theoretical side and the inductive approach in presenting the applied side in the General Company for Plant Industries. The research reached a set of conclusions, the most important of which is that traditional methods are unable to meet the desires of customers and keep pace with developments in the business environment. In addition, the green target costing technique and the product life cycle are contemporary techniques that contribute significantly to helping economic units grow and continue and achieve one of the most important dimensions. The competitive advantage of reducing costs.